Cost‐effectiveness of non‐pharmacological interventions for patients with dementia: A systematic review and meta‐analysis. (31st December 2021) - Huo, Zhaohua; Chan, Joyce YC; Lin, Jiaer; Bat, Baker Kwok Kwan; Chan, Tak Kit; Tsoi, Kelvin KF; Yip, Benjamin HK
Abstract: Background: Non‐pharmacological interventions are widely used in the treatment of dementia, however, the cost‐effectiveness of them remains unclear. This study aimed to review and synthesize the economic evidence of non‐pharmacological interventions for patients with dementia (PwDs). Method: Trial‐based studies evaluating both the costs and effects of non‐pharmaceutical interventions for PwDs were searched from PubMed, Web of Science, EconLit, NHS EED and other five relevant databases. Study quality was assessed using the Cochrane Risk of Bias Tool and the Consensus on Health Economic Criteria list. Cost data were standardized in 2020 US dollars and analyzed from the healthcare perspective. Random‐effects models were used to synthesize the incremental cost and effects of different interventions, based on mean differences (MDs) or standardized mean differences (SMDs). Result: Thirty‐one eligible studies were identified from 40, 587 records. The follow‐up periods ranged from post‐discharge to three years. Care coordination and case management programs brought significant savings of $314 (95%CI: $47 to $582) per person in total healthcare cost, alongside more quality‐adjusted life years (QALYs) gained for PwDs (SMD: 0.197; 95%CI: 0.050 to 0.344). Cognitive‐oriented therapy improved patients' cognitive functions (SMD: 0.105; 95%CI: 0.006 to 0.204), whereas psychological intervention and behavioral management improved the neuropsychiatric symptoms (SMD: 0.109; 95%CI: 0.033 to 0.185). However, they were accompanied with significant increases in total healthcare cost, $490 (95%CI: $70 to $910) and $338 (95%CI: $238 to $438), respectively. Psychological intervention and behavioral management also deteriorated patients' activity functions (SMD: ‐0.195; 95%CI: ‐0.360, ‐0.030). Conclusion: Care coordination and case management for PwDs are most likely to be cost‐effective with lower healthcare cost and better QALYs gained. The acceptance of cognitive‐oriented therapy, psychological intervention and behavioral management depends on the society's willingness to pay for the improvements in patients' health. More economic evidence is required on other types of interventions, such as physical exercise, occupational therapy, and day care program.